Circulating fatty acid binding protein 4 concentration increases with an acute maximal exercise independently of exercise training status - Numao, S.; Uchida, R.; Kurosaki, T.; Nakagaichi, M. (International Journal of Sport & Health Science, 2020)
Limited data on the response of fatty acid binding protein 4 (FABP4) to acute exercise are available. The purpose of this study was to determine the response of FABP4 to incremental maximal exercise in exercise-trained and untrained men. Eleven exercise-trained young men (T group; age, 20.4 ± 1.2 years) and 9 untrained young men (UT group; age, 20.7 ± 0.5 years) performed an incremental maximal exercise after a 12-h fasting period. Before and immediately after the incremental maximal exercise, venous blood was drawn to measure circulating FABP4, free fatty acid, and glycerol concentrations. Body composition, and aerobic capacity were also assessed. Glycerol concentration significantly increased during the exercise in the T group (group × time interaction: p = 0.034; group effect, p = 0.088; and time effect, p = 0.003), and the percentage increase in glycerol concentration was greater in the T group than in the UT group (p = 0.046; ES(r): 0.45). Although circulating FABP4 concentration significantly increased in the two groups (group × time interaction: p = 0.766; group effect, p = 0.114; and time effect, p = 0.001), the percentage increase in FABP4 concentration was similar (p = 0.210; ES(r): 0.28). Additionally, the change of FABP4 concentration was not correlated with that of glycerol (r = - 0.04, p = 0.872). These results indicated that circulating FABP4 concentration increased during incremental maximal exercise regardless of difference in lipolysis and exercise training status in healthy young men.